PENERAPAN TEKNOLOGI MANAJEMEN PENGELOLAAN SAMPAH DI KAMPUNG INSPIRASI JATIBARU DESA JATIENDAH, KABUPATEN BANDUNG - Raharja, Apriadi Budi; Pirngadi, Budi Heri; Darmawan, Fajar (Universitas Mataram, 2024)
The active participation of all community members in managing waste in the RW 17 neighborhood of Jariendah Village, Cilengkrang District, Bandung Regency, is like an